2020
DOI: 10.1021/acsami.0c09706
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Field-Effect Transistors and Ternary Inverters Using Cross-Type WSe2/MoS2 Heterojunctions Treated with Polymer Acid

Abstract: The electrical and optical characteristics of two-dimensional (2D) transition-metal dichalcogenides (TMDCs) can be improved by surface modification. In this study, distinctive field-effect transistors (FETs) were realized by forming cross-type 2D WSe2/MoS2 p–n heterojunctions through surface treatment using poly­(methyl methacrylate-co-methacrylic acid) (PMMA-co-PMAA). The FETs were applied to new ternary inverters as multivalued logic circuits (MVLCs). Laser confocal microscope photoluminescence spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Beyond the effects on individual TMD layers, organic functionalization may also control the electronic properties of TMD-based heterostructures. 33,94 For example, Kim et al reported that the hole conductance of WSe 2 /MoS 2 p–n heterojunction FETs may be enhanced by functionalizing poly(methyl methacrylate- co -methacrylic acid) (PMMA- co -PMAA) on the TMD heterolayers (Fig. 6e).…”
Section: Properties Of Hybrid Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the effects on individual TMD layers, organic functionalization may also control the electronic properties of TMD-based heterostructures. 33,94 For example, Kim et al reported that the hole conductance of WSe 2 /MoS 2 p–n heterojunction FETs may be enhanced by functionalizing poly(methyl methacrylate- co -methacrylic acid) (PMMA- co -PMAA) on the TMD heterolayers (Fig. 6e).…”
Section: Properties Of Hybrid Structuresmentioning
confidence: 99%
“…38,92 Lastly, it was recently reported that the organic functionalization may tailor not only the properties of the individual layer but also the interlayer interaction in TMD-based heterojunctions such as TMD/TMD, TMD/graphene, and TMD/hBN. 90,93,94 The organic layers embedded in the multicomponent heteroassemblies can control the interlayer charge and energy transfer. 93,94 The embedded molecular systems also modify the emission characteristics of IXs in TMD/TMD heterostructures by converting the charge transfer pathways from tunneling to type-II-junction-supported transport and modulating the dielectric screening strength.…”
Section: Organic-integrated Tmd Hybridsmentioning
confidence: 99%
“…The TR-PL spectra were obtained using a time-correlated single-photon counting system. The LCM PL and TR-PL spectroscopy methods were reported in detail in previous works. , The optical absorption spectra of pristine and FPS-K-treated MoSe 2 and WS 2 samples were measured using an Agilent 8453 UV–vis spectrophotometer. The binding energies of the constituent atoms of the samples were measured using X-ray photoelectron spectroscopy (XPS; Nexsa).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…For instance, negative-differential conductance (NDC) devices and negative-differential transconductance (NDT) transistors, which comprise diverse kinds of materials ( e.g. , biomolecule complexes, organic materials, carbon nanotubes, graphene, , van der Waals heterostructures, oxide composites, , silicon (Si) nanostructures, etc . ), are typical examples that can realize the MVL computing system beyond modern binary digital technology.…”
Section: Introductionmentioning
confidence: 99%